Simulation of trace metals and PAH atmospheric pollution over Greater Paris: Concentrations and deposition on urban surfaces. (October 2017) - Thouron, L.; Seigneur, C.; Kim, Y.; Legorgeu, C.; Roustan, Y.; Bruge, B.
Abstract: Urban areas can be subject not only to poor air quality, but also to contamination of other environmental media by air pollutants. Here, we address the potential transfer of selected air pollutants (two metals and three PAH) to urban surfaces. To that end, we simulate meteorology and air pollution from Europe to a Paris suburban neighborhood, using a four-level one-way nesting approach. The meteorological and air quality simulations use urban canopy sub-models in order to better represent the effect of the urban morphology on the air flow, atmospheric dispersion, and deposition of air pollutants to urban surfaces. This modeling approach allows us to distinguish air pollutant deposition among various urban surfaces (roofs, roads, and walls). Meteorological model performance is satisfactory, showing improved results compared to earlier simulations, although precipitation amounts are underestimated. Concentration simulation results are also satisfactory for both metals, with a fractional bias <0.5. Concentrations of benzo[ a ]pyrene are overestimated, probably because continental emissions may be overestimated. Concentrations of benzo[ b ]fluoranthene and indeno[1, 2, 3, cd ]pyrene are underestimated, in part because of null boundary conditions. PAH deposition fluxes are consistent with earlier measurements obtained in the Greater Paris region. The model simulation results suggest that both wet and dry deposition processes need to be considered when estimating the transfer of air pollutants to other environmental media. Dry deposition fluxes to various urban surfaces are mostly uniform for PAH, which are entirely present in fine particles. However, there is significantly less wall deposition compared to deposition to roofs and roads for trace metals, due to their coarse fraction. Meteorology, particle size distribution, and urban morphology are all important factors affecting air pollutant deposition. Future work should focus on the collection of data suitable to evaluate the performance of atmospheric models for both wet and dry deposition with fine spatial resolution. Highlights: Meteorology and air pollution modeling from Europe to Greater Paris. Urban canopy sub-models to represent the effect of the urban morphology. Comparison with a standard roughness-length approach for deposition. A specific case study: deposition over urban surfaces for 3 real urban morphologies. Simulation of trace metals and PAH concentrations and depositions.